Analysis of Appositive Endocentric Phrases on Online Media Websites "Literature Is Officially Entered In the School Curriculum as an Effort to Grow Literacy Skills" - Serli, Serli; Amri, Yusni Khairul (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
This research aims to explain the use of appositive endocentric phrases in the online media opinion "Literature is officially entered in the school curriculum as an effort to grow literacy skills" May 21 2024 Edition. This statement contains the pattern and format of appositive endocentric phrases. Contains all important sentences used in the Indonesian online media "Literature is officially entered in the school curriculum as an effort to grow literacy skills" May 21 2024 Edition, is the object of this research. Data collection techniques use library, reading and note-taking methods. This research reveals that there are many types of phrases including appositive endocentric phrases. This research helps develop a syntactic theory of phrases, especially appositive endocentric phrases, and expands our knowledge of appositive endocentric phrases.